PROCESSES AND OBSTACLES IN LEARNING READING UNDERSTANDING USING THE KWLA STRATEGY - Prihatin, Yulianah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study aims to determine the processes and obstacles in learning to read comprehension using the KWLA (Know, What, Learning, and Affect) strategy. The learning process goes through two cycles, namely cycle I and cycle II, while the intended obstacles are the obstacles experienced by lecturers, students and the environment during the learning process. This research approach uses qualitative descriptive methods. As for the object of research is learning or lecturing reading skills and the research subjects are students of third semester Indonesian Language and Literature Education, Faculty of Education, Hasyim Asy’ari University, totaling eighteen people, 13 girls and 5 boys. The resulting data will be analyzed. Data collection techniques used: survey techniques, recording techniques, observation techniques and note taking techniques. Data analysis techniques used data reduction techniques, data presentation, conclusing drawing / verification. The results showed that during the learning process the obstacles experienced by lecturers, students and the environment were reduced from cycles I and II.